PENERAPAN PENDEKATAN CONTEXTUAL TEACHING AND LEARNING (CTL) UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS V SD NEGERI 9 PEKANBARU - Della Ramadhany; Eddy Noviana; Hendri Marhadi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract : The problem in this research is the low students achievement on social studies V grade students of SDN 9 Pekanbaru with average 71,80 and clasical completeness 44,00% within Minimum Criteria Completeness (KKM) stipulated by schools is 75. The study is in the form of classroom action research (PTK) which aims to improve students achievement on social studies V SDN 9 Pekanbaru with the application of the approach Contextual Teaching and Learning (CTL). After applied the approach Contextual Teaching and Learning (CTL) increased student learning outcomes in UAS I with an average 74.40 with a large increase from basic score 2.60% with classical completeness amounted to 60.00% (not completed) the average UAS II was 79.80 with a large increase from basic score of 8.00% with classical completeness 84.00% (completed). The average percentage of the activity of teachers in the first cycle of the first meeting is 56.25% with sufficient category and then increased by 12.5% in the second meeting be 68.75% with the good category. At the second cycle of the first meeting the average percentage of the activity of teachers increased by 6.25% to 75% with the good category and at the second meeting increased by 12.5% to 87.5% with very good category. Besides the activity of students in the first cycle the first meeting with the average percentage was 56.25% with sufficient category increased by 6.25% in the second meeting to 62.5% with the good category. At the second cycle of the first meeting the average percentage of the activity of students increased by 12.5% to 75% with the good category and at the second meeting increased by 12.5% to 87.5% with very good category. Based on these results it can be concluded that the application of the approach of Contextual Teaching and Learning (CTL) can improve learning outcomes social studies V grade students of SDN 9 Pekanbaru.Key words: Contextual Teaching and Learning (CTL), Students Achievement the Result Of Social Studies